Redescriptions of Neanthes Kinberg, 1865 (Annelida: Errantia: Nereididae) species from worldwide regions - Villalobos-Guerrero, Tulio F.; Kara, Jyothi; Idris, Izwandy (European Journal of Taxonomy, 2021)
The present study redescribes four species of Neanthes Kinberg, 1865 (Nereididae de Blainville, 1818) based on their type specimens collected from different worldwide localities: Neanthes chilkaensis (Southern, 1921) from India, N. galetae (Fauchald, 1977) from Panama, N. helenae (Kinberg, 1865) from St Helena Island, and N. mossambica (Day, 1957) from Mozambique. The morphology of the types was re-examined for the first time after the species were originally described, and incorporated the recent improvements in the standards and terminology for describing nereidid features. The arrangement of paragnaths on area VI stood out among the diagnostic features used to distinguish these four species. Neanthes chilkaensis and N. helenae are the unique nereidids bearing p-bar paragnaths on the area VI. Both species are also distinctive as the former species only exhibited p-bar paragnaths on the area VII–VIII and the latter ventrolateral projections on the apodous segment. Further examination revealed that N. nanciae (Day, 1949) from St Helena is a junior synonym of N. helenae. Moreover, N. galetae and N. mossambica are distinguishable from other species also by the development of dorsal cirri, neuropodial postchaetal lobe and ventral ligule, the presence/absence of merged paragnaths on area IV, paired oesophageal caeca, among other features. This study has further contributed to the morphological delimitation of the species in Neanthes as a first step towards revising the genus.